Coco avant Chanel [videorecording (DVD)] = Coco before Chanel - Fontaine, Anne; Nivola, Alessandro; Tautou, Audrey, 1976-; Devos, Emmanuelle; Gillain, Marie, 1975- (Sony Pictures Classics ; Sony Pictures Home Entertainment, 2009)
Years after being abandoned at an orphanage by her father, Gabrielle Chanel finds a job in a tailor shop where she meets, and soon begins an affair with French millionaire Etienne Balsan. Through Baron Balsan she is introduced into French society and given the opportunity to design her own style of hats. Though her career takes off, her personal life becomes more complicated when she falls in love with Balsan's former best friend Arthur Capel.